Optimization of Pulse Duration Parameter for Hela Cells Growth Rate - Abdul Jamil, Muhammad Mahadi; Zaltum, Mohamed Ahmed Milad; Abd Rahman, Nur Adilah (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
To introduce a cell or tissue with a gene or DNA, electroporation parameter plays the most important role. Research on electroporation parameters is still in its early stages. Different researches have used different parameters while performing their research. Electroporation is a mechanism of temporarily disrupting the bilayer membrane, in such a way that a hydrophilic pore is established, allowing a pathway into the cell for molecules such as DNA, which then heals up, once again protecting the cell from the outside. There are many theories as to how this can occur, but the simplest view is that a short pulse creates an increase in the trans-membrane potential which if it exceeds a certain threshold (dependent on size and shape of cells) can lead to a thinning of the bilayer, either due to a local dislocation in the membrane. In this study, cervical cancer cells (HeLa cells) was used to expose to single pulse electric field. Thus, for the purpose of this study, the field strength of 1kV/cm was selected and the pulse duration was varied (30µs, 70µs, 100µs, 200µs, 300µs and 600µs) to obtain higher proliferation for a growth rate of HeLa cells. From this study, it is determined that, HeLa cell exposed to 1kV/cm with a pulse duration of 100µs and single pulse revealed the highest and fastest percentage confluence when compared to growth rate of HeLa cell exposed for 30µs, 70µs, 200µs, 300µs and 600µs pulse duration.